Eksternalitas Wisata Taman Mini Gayo Indah (TMGI) terhadap Pelaku Usaha di Desa Reli, Kecamatan Blangkejeren, Kabupaten Gayo Lues - Kasmawati Kasmawati; Rinaldi Syahputra; Puti Andiny (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the externalities of Taman Mini Gayo Indah (TMGI) tourism on the welfare of the local community in Reli village, Blangkejeren District, Gayo Lues Regency. The focus of this research is on the socio economix, socio cultural, and physical environmental impacts experienced by the community who carry out activities around the tourism area. The method used in this study is a qualitative descriptive analysis. Data were collected though indepth interviews and essay questionnaires involving 9 respondents consisting of food vendors, beverage sellers, stall owners, and children’s play service providers around the tourist area. The results of the study show that the existence of Taman Mini Gayo Indah tourism provides positive impacts on the socio economic aspects of the community, particularly through the creation of business opportunities and increased income for local community and tourists can broaden community insights and social experiences. However, in the physical environmental aspect, several negative impacts were identified, such as an increase in waste and higher visitor density at certain times. Overall, the existence of TMGI contributes to improving the welfare of the community in Reli village.